1989
DOI: 10.1515/zna-1989-0409
|View full text |Cite
|
Sign up to set email alerts
|

Structural Phase Transitions and Ionic Motions in Pyridinium Hexachlorotellurate(IV),Hexachlorostannate(IV), and Hexabromostannate(IV) Crystals as Studied by 1H NMR

Abstract: in P y rid in iu m H e x a c h lo r o te llu r a te ( I V ) , H e x a c h lo r o s ta n n a te ( I V ) , a n d H e x a b r o m o s ta n n a te ( I V ) C r y s ta ls a s S tu d ie d b y N M R Yutaka Tai, Tetsuo Asaji, Ryuichi Ikeda*, and Daiyu Nakamura Department of Chemistry, Faculty of Science, Nagoya University, Chikusa, Nagoya, Japan Z. Naturforsch. 44 a, 300-306 (1989); received January 21, 1989The 'H NMR second moment M2 and the spin-lattice relaxation time T, are determined for pyridinium hexachlorotellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…Displacement ellipsoids are drawn at the 50% probability level. Table 2 Fractional atomic coordinates and displacement parameters (Å 2 ) for the low-temperature phase of (C 5 H 6 N) 2 (15) to explain the temperature dependence of M 2 by assuming a three-wells potential model with minima at G308 rotated positions instead of G608 rotated positions. The M 2 reduction factor, R M 2 Z hM motion 2 i p =hM rigid 2 i p , was observed to be about 0.7 at T c Z241 K as shown in Fig.…”
Section: Change In the Potential Energy For The Reorientational Motiomentioning
confidence: 99%
See 1 more Smart Citation
“…Displacement ellipsoids are drawn at the 50% probability level. Table 2 Fractional atomic coordinates and displacement parameters (Å 2 ) for the low-temperature phase of (C 5 H 6 N) 2 (15) to explain the temperature dependence of M 2 by assuming a three-wells potential model with minima at G308 rotated positions instead of G608 rotated positions. The M 2 reduction factor, R M 2 Z hM motion 2 i p =hM rigid 2 i p , was observed to be about 0.7 at T c Z241 K as shown in Fig.…”
Section: Change In the Potential Energy For The Reorientational Motiomentioning
confidence: 99%
“…The potential well for the pyridinium reorientation in the low-symmetric crystal phase, has been discussed by the model of reorientation between inequivalent potential wells [12,[14][15][16][17][18]. Kozak et al showed by NMR study that the energy difference, which characterizes the inequivalence of the wells, is a function of temperature in pyridinium hexafluorophosphate [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have studied the dynamics of molecular ions in pyridinium tetrachloroaurate(III) and pyridinium hexachlorometallates(IV) by chlorine NQR and proton NMR experiments [4][5][6][7], In these complexes, an unusual relaxation mechanism was found on measuring the 35 C1 NQR spin-lattice relaxation time T 1Q and the NMR spin-lattice relaxation time Ti. That is, it was shown that the relaxation mechanisms of the chlorine and hydrogen nuclei are fluctuations of the electric field gradient (EFG) due to cationic motions and fluctuations of the local magnetic field due to anionic motions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Reorientation of ions in crystals has extensively been studied by *H NMR and NQR experiments for the pyridinium cation (pyH + ) in (pyH)X (X = C1, Br, I) [1][2][3], (pyH)AuX4 (X = C1, Br) [4,5], and (pyH)2MX6 (M =Te, Sn; X = C1, Br) [6][7][8]. In these crystals, except for (pyH)AuX4, structural phase tran sitions have been detected and discussed [1][2][3][6][7][8],…”
Section: Introductionmentioning
confidence: 99%
“…In these crystals, except for (pyH)AuX4, structural phase tran sitions have been detected and discussed [1][2][3][6][7][8],…”
Section: Introductionmentioning
confidence: 99%